Design of Integrated Wireless Communication System for Autonomous-rail Rapid Transit - LI Yuan; HU Yunqing; ZHANG Heng; CHEN Yang; ZHANG Nan (Kongzhi Yu Xinxi Jishu)
Integrated wireless communication system is mainly responsible for the communication, data transmission and voice call function between rail vehicle and its ground system. In this paper, according to the requirements of autonomous-rail rapid transit, a customized system scheme and functional requirements are designed using 4G public network or self-built private network mode to realize functions such as train to ground data transmission, voice call, data security management and so on. Actual project verification results show that this scheme can effectively carry the train operation, production and operation, passenger service and other customer service related business.